Pola Komunikasi Orang Tua Dalam Mengawasi Penggunaan Gawai Pada Anak Usia Dini di Kecamatan Batang Kuis - Silvia Wahyuni; Junaidi Junaidi (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
The use of gadgets by children who are not supervised can be bad for their growth and development. To prevent children from being exposed to inappropriate content, communication within the family needs to be built harmoniously in order to get a good education for children. The purpose of this study was to find out how parents communicate to provide an understanding of what can and cannot be done when children play with gadgets and to find out what efforts parents make in supervising the use of gadgets by children. In this study, the theory used is that of Ascan Koerner and Mary Ann Fitzpatrick, who argue that parental communication patterns are categorized into three categories: permissive communication patterns, authoritarian communication patterns, and authoritative communication patterns. The method used in this research is a qualitative descriptive method. The results of this study show that every parent has their own way of communicating with their children. namely by using permissive communication patterns and authoritative communication patterns.